VD_FINDINFO Décision / 2014 / 510 vom 13. Juni 2014 - VD Tribunal cantonal (2014)
FICTION DE LA NOTIFICATION, NOTIFICATION DE LA DÉCISION, NOTIFICATION IRRÉGULIÈRE | 354 CPP (CH), 88 al. 1 let. a CPP (CH), 88 al. 1 let. c CPP (CH), 88 al. 4 CPP (CH)